Overview Of Knowledge On How To Brush Your Teeth On Ohi-S Status Students At Inpres Pannara Primary School, Manggala Kota District Makassar - B, Sangkala; Annisa, Nurul; Qalbi, Astri Annur; Lakoro, Khalifa Zalsabila; AR, Aisyah (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Dental and oral health is important for the general health and well-being of the body and greatly influences the quality of life. Dental and oral health problems will have an impact on a person's performance. Brushing your teeth in the morning after eating and at night before going to bed is an effort to maintain oral hygiene. The purpose of brushing teeth is to remove plaque and the entire surface of the teeth. Efforts to maintain oral hygiene and foster dental health, especially for school-aged children, need special attention because at this age children are undergoing a process of growth and development. The type of research that will be carried out is descriptive research with the aim of seeing a picture of knowledge of how to brush teeth on OHI-S status among students at SD Inpres Pannara, Manggala District, Makassar City. From the results of research conducted on students at SD Inpres Pannara in November 2023 by filling out questionnaires by students at SD Inpres Pannara with a total of 50 students and carrying out dental and oral hygiene checks. Data obtained from respondents' knowledge was good with a total percentage of knowledge of 63% in the good category, 38% in the medium category, and 0% in the poor category, then for OHI-S status they got the good category with a percentage of 6% in the good category, in the medium category 82%. and the bad category is 12%.